PRELUDE TO THE CAMBRIAN EXPLOSION - Valentine J.W. (My University, 2002)
The Prelude began with the origin of Metazoa, perhaps between 720 and 660 million years ago (mya), and ended with the geologically abrupt appearance of crown bilaterian phyla that began between 530 and 520 mya. The origin and early evolution of phyla cannot be tracked by fossils during this interval, but molecular phylogenetics permits reconstruction of their branching topology, whereas molecular developmental evidence supports hypotheses for the evolution of the metzoan genome during the rise of complex bodyplans. A flexible architecture of genetic regulation was in place even before the appearance of crown sponges, permitting increases in gene expression events as bodyplan complexity rose. Neoproterozoic bilaterians were chiefly small-bodied but likely diverse, whereas in the earliest Cambrian, between 543 and approximately 530–520 mya, bodies that were complex by marine invertebrate standards evolved in association with body-size increases.
Keywords: Metazoa; body fossils; trace fossils; phyla; developmental evolution; Cambrian; Paleozoic::Cambrian; Палеозой::Кембрийская